Applied Hierarchical Cluster Analysis with Average Linkage Algoritm - Astuti, Cindy Cahyaning; Untari, Rahmania Sri (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2017)
This research was conducted in Sidoarjo District where source of data used from secondary data contained in the book